Antibiotic resistance in wastewater, does the context matter? Poland and Portugal as a case study - Vaz-Moreira, Ivone (2022)
Antibiotic resistance has been considered a major human health threat that may endanger the success of medicine. Recent studies have unveiled worldwide asymmetries of antibiotic resistance occurrence, being factors as diverse as climate, socioeconomic, or antibiotic use possible drivers of such asymmetric distribution. In Europe, where clinical antibiotic resistance is surveyed for more than 20 years, the European Center for Disease Prevention and Control (ECDC) consistently describes an increasing gradient from North-to-South and from West-to-East. This observation motivated the current perspective paper aiming to qualitatively compare two countries located at the extreme latitude of Europe and also at distant longitude - Poland in the Central-East region and Portugal in the South-West. Both countries have been among those with the highest prevalence of antibiotic resistance in clinical settings, although as it is discussed, climate, socioeconomic factors, and antibiotic use are different. In general, in Poland higher antibiotic consumption and resistance prevalence is observed, mainly at the community level, when compared to Portugal. However, in Portugal, treated wastewater may hold identical or slightly higher resistance loads. Based on these observations, it is discussed how different factors may influence the abundance of antibiotics, antibiotic resistant bacteria, and genes in wastewater before and after treatment.